Usaha Ternak Itik Petelur di Sentra Produksi di Kabupaten Kediri dan Kelayakan Finansialnya - Nur Khabibi; Wiwiek Andajani; Tutut Dwi Sutiknjo; Nina Lisanty (JINTAN : Jurnal Ilmiah Pertanian Nasional, 2022)
The demand for animal products in Indonesia increases public awareness of the need for better food nutrition. Therefore, the livestock business plays an important role and needs to be developed from agribusiness. The study was conducted in an independent laying duck business in Tegalan Village, Kandat District, Kediri Regency, to analyze the business's financial feasibility. The analysis was carried out descriptively and quantitatively. The analytical tools included the Internal Rate of Return (IRR), Payback Period (PP), and sensitivity analysis. The data in the field were divided into three categories, namely breeders with a category of fewer than 500 ducks (A), a category of 500–1000 ducks (B), and a category of more than 1000 ducks (C). The results of the analysis based on the value (IRR) of the three categories of breeders showed a higher value than the percentage of bank interest (14%), where breeders in category A (374 ducks) had an IRR of 87%, category B breeders (650 ducks) of 112 %, and breeders in category C (2,275 ducks) were 54%. Meanwhile, in terms of PP, the three categories of breeders were when the project is not over (less than 10 years), category A breeders needed a payback period of 1.7 years, category B breeders for 1.2, and category C breeders for two years. Permintaan produk hewani di Indonesia semakin meningkat seiring dengan kesadaran masyarakat akan kebutuhan gizi pangan yang lebih baik. Oleh karenanya, usaha ternak menjadi bagian penting dan perlu pengembangan dari sisi agribisnisnya. Penelitian dilakukan di suatu usaha ternak itik petelur mandiri di Desa Tegalan, Kecamatan Kandat, Kabupaten Kediri untuk menganalisis kelayakan finansial usahanya. Analisis dilakukan secara deskriptif dan kuantitatif. Alat analisis yang digunakan di antaranya adalah Internal Rate of Return (IRR), Payback Period (PP), dan analisis sensitivitas. Data di lapangan dibagi menjadi tiga kategori, yaitu peternak dengan kategori jumlah ternak kurang dari 500 ekor (A), kategori 500–1000 ekor (B), dan kategori lebih dari 1000 ekor (C). Hasil analisis berdasarkan nilai (IRR) dari ketiga kategori peternak menunjukkan nilai yang lebih tinggi dari persentase bunga bank (14%), di mana peternak pada kategori A (374 ekor) mempunyai IRR sebesar 87%, peternak kategori B (650 ekor) sebesar 112%, dan peternak dalam kategori C (2.275 ekor) sebesar 54%. Sementara dalam segi PP, ketiga kategori peternak berada pada saat umur proyek belum berakhir (kurang dari 10 tahun), di mana peternak kategori A memakan waktu pengembalian modal selama 1,7 tahun, peternak kategori B selama 1,2 tahun, dan peternak kategori C selama 2 tahun.